Developing Communicative Competence of ESL Learners through Learning Strategies (Journal of NELTA, 2018)
Learning strategies are special behaviors and actions which are employed to develop communicative competence of learners (Oxford, 1990). Second language learners can communicate their ideas, feelings, and emotions through learning strategies: cognitive, metacognitive, memory, social, affective etc. as well as communicative strategies in the process of developing communicative competence. Learning strategies and communicative strategies work as a panacea to develop communicative competence. The researcher conducted an exploratory research through survey to collect data using questionnaire, semi-structured interview and classroom observation to find out the existing learning strategies in developing speaking skills and to discover the attitude of secondary level teachers towards learning strategies and communicative strategies in developing communicative competence of learners. He selected 30 secondary level teachers as sample population of the study. The findings of the study were: a) the teachers did not use collaborative learning and scaffolding techniques to help the learners develop speaking skills, b) they were unable to employ collaborative learning, group discussion, and peer talking owing to overcrowded classes and time-constraint; most of the teachers taught speaking skill without using language functions, c) there is positive attitude of secondary level teachers towards learning strategies and communicative strategies to develop communicative competence of learners. Journal of NELTA, Vol 20 No. 1-2, December 2015 , Page:51-62